A Global Empirical Model of Electron Density Profile in the F Region Ionosphere Basing on COSMIC Measurements. Issue 4 (16th April 2021) - Li, Qiaoling; Liu, Libo; He, Maosheng; Huang, He; Zhong, Jiahao; Yang, Na; Zhang, Man‐Lian; Jiang, Jinzhe; Chen, Yiding; Le, Huijun; Cui, Jun
Abstract: The topside ionosphere accounts for a dominant part of the ionospheric total electron content, whereas accurate global modeling of topside ionospheric electron density (Ne) profile has not been fully achieved. In this study, a high precision Ne profile model, named α‐Chapman Based Electron Density Profile Model (α‐Chapman‐Based‐EDP), was built by using ∼4.5 million Ne profiles from the Constellation Observing System for Meteorology, Ionosphere, and Climate (COSMIC‐1) radio occultations. We first describe each of the profiles using five parameters of the α ‐Chapman function, that is, peak density (NmF2) and height (hmF2) of F2 layer, scale height (Hm) as well as its altitude change rates, and then built a model for each of the parameters as a function of latitude, longitude, month, local time, and solar activity, through Empirical orthogonal function (EOF) analysis and Fourier expansion. Combining all the five models, we construct the α‐Chapman‐Based‐EDP. Compared with observations from COSMIC‐1 and ‐2, the model captures the ionospheric climatology well, such as solar activity dependence, seasonal variation, and spatial pattern, including the equatorial ionization anomaly and midlatitude trough as well as their variabilities. Our model can describe nearly 80% variability of Ne in F region. In contrast, the IRI2016 cannot well reproduce these characteristics, with errors higher than our model. The potential applications of our model were also discussed. A dense matrix data calculated by the model will be released in https://www.researchgate.net/profile/Qiaoling_Li5 with the permissions of COSMIC organizations. Key Points: A global model of Ne profile in F region ionosphere was constructed based on the α ‐Chapman function The model gives three‐dimensional Ne as well as five key parameters of Ne profile, including NmF2, hmF2, Hm, and its change rates with height The model reasonably reproduces the equatorial ionization anomaly and midlatitude trough